FDI and income inequality in ASEAN-5 countries: a quantile regression approach - Mahamad Zakaria, Muhammad Farhan; Wan Ngah, Wan Azman Saini; Law, Siong Hook (2014)
The purpose of this paper is to analyse the impact of FDI inflows on income distribution in ASEAN-5 countries (Indonesia, Malaysia, Philippines, Singapore, and Thailand). Specifically, it investigates whether the inflows of FDI is associated with a greater income inequality within these countries. The empirical results, based on quantile regression analysis and data over 1970-2011 period, reveal that FDI inflows have an inequality-reducing effects in Malaysia, the Philippines and Thailand. However, the findings for Singapore and Indonesia suggest that FDI perpetuates inequality.